2020
DOI: 10.3390/cancers13010038
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Chimeric Antigen Receptor Structural Domains on Clinical Outcomes and Associated Toxicities

Abstract: Chimeric antigen receptor (CAR)-T cell therapy has transformed the treatment of B cell malignancies, improving patient survival and long-term remission. Nonetheless, over 50% of patients experience severe treatment-related toxicities including cytokine release syndrome (CRS) and neurotoxicity. Differences in severity of toxic side-effects among anti-CD19 CARs suggest that the choice of costimulatory domain makes a significant contribution to toxicity, but comparisons are complicated by additional differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 65 publications
1
18
0
Order By: Relevance
“…Therefore, [ 89 The sensitivity and clinical applicability of the method was further evaluated in a separate study [90], whereby a detection limit of 1.0 × 10 4 T-cells was observed when imaging was performed on tumour-bearing NSG mice injected with different numbers of transgenic T-cells. This observation at the preclinical level is promising and compatible with the number of human CAR T-cells usually administered into patients for treatment in clinical trials, which is of the order of 10 4 to 10 8 per kilogram body weight [91].…”
Section: In Vivo Imaging Of Cells Using Antibodies (Immuno-pet)supporting
confidence: 56%
See 1 more Smart Citation
“…Therefore, [ 89 The sensitivity and clinical applicability of the method was further evaluated in a separate study [90], whereby a detection limit of 1.0 × 10 4 T-cells was observed when imaging was performed on tumour-bearing NSG mice injected with different numbers of transgenic T-cells. This observation at the preclinical level is promising and compatible with the number of human CAR T-cells usually administered into patients for treatment in clinical trials, which is of the order of 10 4 to 10 8 per kilogram body weight [91].…”
Section: In Vivo Imaging Of Cells Using Antibodies (Immuno-pet)supporting
confidence: 56%
“…Differential patterns of distribution of [ 89 Zr]Zr-aTCRmu-F(ab')2 signals were detected in the tumours, i.e., larger tumours exhibited intense signals at the tumour border, whilst smaller tumours demonstrated uniform distribution of signals.The sensitivity and clinical applicability of the method was further evaluated in a separate study[90], whereby a detection limit of 1.0 × 10 4 T-cells was observed when imaging was performed on tumour-bearing NSG mice injected with different numbers of transgenic Tcells. This observation at the preclinical level is promising and compatible with the number of human CAR T-cells usually administered into patients for treatment in clinical trials, which is of the order of 10 4 to 10 8 per kilogram body weight[91].Radiolabelled antibodies can also be used for monitoring the efficacy of NK cell therapies. A recent example is the use of radiolabelled IgG1 antibodies specific for the human NK cell activation receptor NKp30, i.e., [64 Cu]Cu-NKp30Ab to detect NK cell trafficking in an adoptive cell transfer model[92].…”
mentioning
confidence: 61%
“…Based on this mechanism, Sun et al [122] added the small molecule AP21967 to a modified SHP1 on the CD28 domain to reduce cytokine release and ameliorate CRS without compromising the antitumor effects. However, a retrospective analysis showed that the incidences of CRS and ICANS are likely to be more related to HD and TMD than the costimulatory domain [123]. The role of the costimulatory domain is still unclear and remains to be clarified in further research.…”
Section: Optimization Of the Car Structurementioning
confidence: 99%
“…In the HER2 CAR used here, CD28 costimulation is explicitly encoded through the CD28 signaling tail incorporated into the CAR protein but is also amplified through a specific sequence signature in the CD28 TMD that recruits endogenous CD28 into activated CAR complexes. This association likely explains a large portion of the enhanced potency and higher toxicity of CD28 TMD-containing CARs compared to those that use TMDs from CD8 or other proteins (Brudno et al, 2020;Cappell and Kochenderfer, 2021;Davey et al, 2020;Fujiwara et al, 2020;Majzner et al, 2020) and underscores the importance of fully understanding the structure-function relationships in natural TMDs when repurposing them for receptor engineering.…”
Section: Discussionmentioning
confidence: 99%